Non‐HLA‐matched 3rd party vascular allograft in renal transplant may lead to sensitization against donor HLA. Issue 11 (7th October 2016) - Watson, Henry; Pande, Rupaly; Farid, Shahid; Ecuyer, Clare; Baker, Richard; Clarke, Brendan; Ahmad, Niaz
Abstract: 3rd party donor vessels are often used for vascular reconstruction in organ transplantation. While current practice ensures that 3rd party vessels are blood group matched, HLA matching to the non‐intended recipient is not performed. This practice potentially sensitizes the recipient and may reduce their future chance of renal transplant from a larger pool of donors. We examined our cohort of renal transplant recipients who received non‐HLA‐matched 3rd party vessels for the de‐novo development of donor‐specific HLA antibodies. Our institution's Human Tissue Authority (HTA) blood vessel registers were examined to identify stored donor vessels and their non‐intended recipients. Donor vessel HLA status was cross‐referenced with the recipient HLA status. Between 2004 and 2014, five patients were identified that received 3rd party non‐HLA‐matched vessels for vascular reconstruction during renal transplantation. Three patients (60%) subsequently developed donor‐specific HLA antibodies. These data provide evidence that use of non‐HLA‐matched stored 3rd party vascular grafts may lead to sensitization in the recipient. Where time permits, HLA matching should be performed to avoid this allogeneic response. Laboratories monitoring DSA should be aware of any patient receiving a non‐HLA‐matched 3rd party vascular graft, and recipients may benefit from increased post‐transplant immunological vigilance.